2019
DOI: 10.1017/s0033291719000904
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation and length of hospital stay following first-episode psychosis: systematic review and meta-analysis of longitudinal studies

Abstract: 2019). Hospitalisation and length of hospital stay following first-episode psychosis: Systematic review and metaanalysis of longitudinal studies. Psychological Medicine. https://doi. AbstractBackground: Reducing hospitalisation and length of stay (LOS) in hospital following first episode psychosis (FEP) is important, yet reliable measures of these outcomes and their moderators are lacking. We conducted a systematic review and meta-analysis to investigate the proportion of FEP cases who were hospitalised after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
4
21
3
1
Order By: Relevance
“…Our finding that 38% of people with early psychosis had an admission within 2 years of first diagnosis is lower than a recent meta-analysis of international estimates, reporting that 55% of patients were hospitalized at least once over any length of follow-up (Ajnakina et al, 2019). This difference may be partially explained by study region, given that subgroup analyses from this review revealed a lower proportion of hospitalized patients in studies from North America (48%; Ajnakina et al, 2019). Comparison with earlier time periods in Ontario health administrative data suggests that differences could also be due to declining hospitalization rates over timewe previously observed that 38% of first-episode cases were hospitalized at first diagnosis between 1999 and 2008 ), compared to 10% in the current study.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Our finding that 38% of people with early psychosis had an admission within 2 years of first diagnosis is lower than a recent meta-analysis of international estimates, reporting that 55% of patients were hospitalized at least once over any length of follow-up (Ajnakina et al, 2019). This difference may be partially explained by study region, given that subgroup analyses from this review revealed a lower proportion of hospitalized patients in studies from North America (48%; Ajnakina et al, 2019). Comparison with earlier time periods in Ontario health administrative data suggests that differences could also be due to declining hospitalization rates over timewe previously observed that 38% of first-episode cases were hospitalized at first diagnosis between 1999 and 2008 ), compared to 10% in the current study.…”
Section: Discussioncontrasting
confidence: 88%
“…Our finding that 38% of people with early psychosis had an admission within 2 years of first diagnosis is lower than a recent meta‐analysis of international estimates, reporting that 55% of patients were hospitalized at least once over any length of follow‐up (Ajnakina et al, ). This difference may be partially explained by study region, given that subgroup analyses from this review revealed a lower proportion of hospitalized patients in studies from North America (48%; Ajnakina et al, ).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…First, the current study used a relatively short CCT as we wanted to keep the intervention duration comparable to the duration of clinical treatment. Our intention was to provide greater resemblance to the real-world clinical setting that appears common in many other health centers across Europe [78], and provides a strong clinical care framework due to the initial stay of the patients at the ward or frequent clinical checks. However, we cannot claim that ROP patients who did not respond with an improvement of rsFC pattern and did not show efficient SPC learning would not achieve neural 'recovery' associated with enhancement of cognition with a slightly different form of intervention, longer duration, or implementing more diverse protocols [7].…”
Section: Discussionmentioning
confidence: 99%